Green Finance and the Sustainable Development Goals: A Review of some International Experiences - Noureddine, Abdelkader (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير - مخبر اقتصاديات الطاقات المتجددة ودورها في تحقيق التنمية المستدامة, 2022)
Financial institutions show more interest in traditional energy projects (oil and gas) than green projects, mainly because there are still many risks associated with these new technologies and provide a lower rate of return, if we want to achieve the sustainable development goals, we need to open New green environment file; By financing green projects and expanding financing for investments that provide environmental benefits, through new financial instruments and new policies, such as green bonds; Green instruments; And green banks; Green banking; And financial technologies, community green funds, etc., which are known collectively as "green financing". In this study, green finance was addressed in some countries, in order to draw lessons from the successful experiences that can be applied in Algeria. These countries have made green finance a political priority, as they have formulated national action plans or "road maps" to transform the economy and the financial sector into a green economy and green finance.
Keywords: الاقتصاد الأخضر -- المؤسسات المالية -- الموارد الطبيعية -- التدفقات المالية -- الخدمات التمويلية